Visualization of interactions between depressurization-induced hydrate decomposition and heat/mass transfer - Kou, Xuan; Feng, Jing-Chun; Li, Xiao-Sen; Wang, Yi; Chen, Zhao-Yang (Energy, 2022)
Visual evidences to understand the interactions between hydrate decomposition and heat/mass transfer are currently lacking. This study proceeds from the hydrate morphology to visualize the interactions between depressurization-induced hydrate decomposition and heat/mass transfer from different scales. Reactor-scale hydrate distribution evolution shows that the dominant influencing factor of hydrate decomposition transforms from heat transfer to mass transfer. More importantly, pore-scale visual ev-idences suggest that the mass transfer of gas shows significant effects on hydrate morphology evolution. Specifically, the limited gas diffusion in liquid phase could lead to the hydrate morphology evolution from patchy pore-filling to "grain-bridging" during hydrate decomposition. The combination of grain-bridging hydrate together with the water layer that wraps the hydrate is termed as "hydrate bridge" in this work. It is also worth noting that the grain-bridging hydrate could accelerate fluid flow in pores according to our seepage simulation results. These findings provide visual evidences for variations in physical properties of hydrate-bearing sediments during hydrate decomposition. Since physical prop-erties of hydrate-bearing sediments play important roles in hydrate decomposition, the hydrate morphology evolution characteristics analyzed here are valuable for hydrate exploitation in field tests. (c) 2021 Elsevier Ltd. All rights reserved.